UJI AKTIVITAS ANTIBAKTERI FRAKSI DARI EKSTRAK TERAKTIF DAUN JENGKOL (Pithecollobium labatum Benth) TERHADAP Pseudomonas aeruginosa ATCC 27853 - Cincin Kirana, Bida (Widya Warta, 2021)
This research aimed to know the antibacterial activity of n-hexane, ethyl acetate, and methanol extracts from the jengkol leaf, which was the most active extract in inhibiting Pseudomonas aeruginosa ATCC 27853 bacteria; to know the fractions from most active extract of jengkol leaf which had antibacterial activity against Pseudomonas aeruginosa ATCC 27853; and to know inhibitory zone broad and the class of compounds contained in most active fraction from most active extract which had antibacterial activity. Maceration of jengkol leaf extract with the soxhlet method in a phased used n-hexane, ethyl acetate, and methanol solvent. The most active extract and fraction were tested for its antibacterial activity using the diffusion method. The most active extract was conducted separation by vacuum column chromatography which eluted gradiently with a solvent of increasing polarity. The separation results were monitored by thin-layer chromatography with the stationary phase of silica gel GF-254 and the mobile phase of chloroform: methanol (2:8). The most active fraction was identified for its chemical content. The research results obtained ethyl acetate extract of jengkol leaf had the greatest antibacterial activity against Pseudomonas aeruginosa ATCC 27853 compared with n-hexane and methanol extract. The most active fraction namely fraction IV, had average inhibitory diameter of 11,33 mm (3000 ppm); 13,33 mm (5000 ppm); 15,33 mm (7000 ppm). The class of chemical compounds contained in fraction IV were flavonoids and saponins.